Heterotrophic N2-fixation contributes to nitrogen economy of a common wetland sedge, Schoenoplectus californicus. - Eliška Rejmánková; Dagmara Sirová; Stephanie T Castle; Jiří Bárta; Heather Carpenter (PLoS ONE, 2018)
A survey of the ecological variability within 52 populations of Schoenoplectus californicus (C.A. Mey.) Soják across its distributional range revealed that it is commonly found in nitrogen (N) limited areas, but rarely in phosphorus limited soils. We explored the hypothesis that S. californicus supplements its nitrogen demand by bacterial N2-fixation processes associated with its roots and rhizomes. We estimated N2-fixation of diazotrophs associated with plant rhizomes and roots from several locations throughout the species' range and conducted an experiment growing plants in zero, low, and high N additions. Nitrogenase activity in rhizomes and roots was measured using the acetylene reduction assay. The presence of diazotrophs was verified by the detection of the nifH gene. Nitrogenase activity was restricted to rhizomes and roots and it was two orders of magnitude higher in the latter plant organs (81 and 2032 nmol C2H4 g DW-1 d-1, respectively). Correspondingly, 40x more nifH gene copies were found on roots compared to rhizomes. The proportion of the nifH gene copies in total bacterial DNA was positively correlated with the nitrogenase activity. In the experiment, the contribution of fixed N to the plant N content ranged from 13.8% to 32.5% among clones from different locations. These are relatively high values for a non-cultivated plant and justify future research on the link between N-fixing bacteria and S. californicus production.